THE EFFECT OF DIVERSITY OF HALAL FOOD PRODUCTS AND PROMOTION ON THE INTEREST OF TOURISTS - Wahyu Ari Indriastuti; Erna Wigati; Tri Wahyuningsih; Muthoifin Muthoifin (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study is to reveal the effect of the diversity of halal food products and promotions on tourist interest. The method used in this research is descriptive qualitative research with the type of field research, which was carried out at the Ciplukan Market, Sendang Ijo Mlilir Gentungan Mojogedang Karanganyar. The results showed that: 1). there is a positive and significant influence on the diversity of halal food products on tourist interest in the Ciplukan market of Sendang Ijo, Gentungan Mojogedang. The more diverse halal food products are sold, the higher the interest of tourists to visit the market, 2). There is a positive and significant effect of promotion on tourist interest. The higher or more intensive the promotion carried out, the higher the interest of tourists to come to visit the market, and vice versa, 3). There is a positive and significant influence on the diversity of halal food products and promotions on the interest of tourists in Ciplukan Market. These two variables together can be used as a basis for predicting tourist interest, 4). The diversity of halal food products is a variable that is a larger contribution to visitor interest than promotion. These two variables together can be used as a basis for predicting tourist interest, 4). The diversity of halal food products is a variable that is a larger contribution to visitor interest than promotion. These two variables together can be used as a basis for predicting tourist interest, 4). The diversity of halal food products is a variable that is a larger contribution to visitor interest than promotion.